STUDY OF THE CURRENT STATE AND TRENDS OF FUTURE TRADING ON THE WORLD STOCK EXCHANGE MARKET (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article discusses the role of futures exchanges in our time. It is a tool used to redistribute value added generated in the investment sector. Because commodity, capital, and currency prices can be optimized, companies that actively use futures are more competitive. The structure of the volume of futures trading by regions is shown. Exchange futures trading has a strong geographical concentration. The main exchanges are located in the world's largest economic centers: the United States, Britain, Japan. The dynamics of futures trading has been studied: the change of commodity futures to financial ones, the monopoly of production and sales, the pricing system, the growing popularity of oil futures contracts. Factors influencing the dynamics of futures trading have been identified.A comparative description of currency and interest rate futures is given. Currency futures are a contract under which a certain amount of foreign currency is delivered on the day of execution. Interest rate futures are futures contracts on fixed income securities, the prices of which largely depend on current and projected interest rates. Interest rate futures are futures contracts on fixed income securities, the prices of which largely depend on current and projected interest rates. Short-term interest rate futures refer to futures contracts based on short-term interest rates, such as bank interest rates on government short-term bonds for up to one year. Long-term interest rate futures are a standard exchange contract used to buy and sell standard and quality bonds at a price agreed during the transaction on a specified date in the future.Prospects for the development of the futures market in Ukraine have been identified. It is concluded that in different regions of the world the use of futures trading has a direct impact on the formation of market conditions, so the use of futures contracts in modern realities shows the need for future development of the stock market in Ukraine. In particular, trade in derivatives for Ukrainian agricultural products should not take place on foreign trading platforms, but on domestic exchanges.The country, which owns 40% of the world's chernozem reserves and is already a leading exporter of many agricultural products, has the right and must independently form world prices for these strategic products. According to the results of the 2019-2020 marketing year, Ukraine in total in terms of exports of all cereals became the second largest exporter in the world after the United States.
Keywords: futures, futures contract, futures market, futures trading, stock market